Aerial Wanderings and Mountain Territorialities: Geographical Reflections on Cross-Country Paragliding - Camille Girault (Revue de Géographie Alpine)
The present paper focuses on cross-country paragliding, a form of “aerial wandering” whose goal is to use the lift provided by rising air currents to accomplish long circuits or journeys. A detailed description of the sport is followed by an analysis of pilots’ singular relationship with airspace, which results from the paradoxes of cross-country paragliding and the fact that every flight inevitably includes detours: A straight line is never the most efficient or effective route, even in the air. Moreover, the conflict between the sport’s recreational and contemplative dimensions and its performance and competitive dimensions, combined with the intangible factors (air conditions, rules governing airspace) that constrain pilots’ liberty of movement, mean that paragliding is not quite as synonymous with freedom as one might think. Finally, the way in which pilots appropriate the areas over which they fly results in cross-country paragliding producing its own territorialities. These territorialities can be studied by analysing written and filmed accounts of long-distance flights, which express the experiential aspects of free-flying and of viewing the Earth from the sky.